TEKNIK MOTION GRAPHICS PADA VIDEO PROFIL PRODI INFORMATIKA UNIVERSITAS MAJALENGKA - Nana Sutrisna; Ade Bastian (J-ENSITEC, 2021)
The rapid development of information technology has had a positive impact on the general public. Company profile is an explanation of the agency in general. It contains information, vision, and mission of an agency. Company profile has an important role for an agency because it can present the vision and mission of the agency or what it wants to offer. The company profile video is the most complete media, because the video has an element of motion, a real visualization. In addition, the benefits of this company profile video are as a presentation tool to shorten the meeting so there is no need to ask in detail about the agency's profile, vision and mission. Motion graphics is a branch of graphic design, where in motion, design elements such as shape, shape, size, direction, texture contained in it, are intentionally moved or given movement to make it look alive. It is very interesting to promote agencies with motion graphics and information and promotion media have been made in the form of a company profile video for the Informatics Study Program, Majalengka University. Which consists of 6 scenes with a video duration of 1 minute 42 seconds. As a promotional media about the Universitas Majalengka Informatics Study Program to the general public.